Trade, Trust and Transaction Cost - Frank A.G. den Butter; Robert H.J. Mosch (Tinbergen Institute, 2003)
Transaction costs are a major reason why international trade flows are much smaller than traditional trade theory would suggest. Trust between trading partners lowers transaction costs and may therefore enhance trade. The empirical analysis of this paper shows that more trust leads to more trade so that part of the mystery of missing trade can be attributed to the lack of trust between trading partners, e.g. because of cultural differences and habits, or because of insufficient information on product quality and reliability. Our gravity equation estimates for 25 countries show that measures of both formal and of informal trust contribute to the explanation of bilateral trade flows. When we assume an increase in informal trust by one standard deviation, the combined effects of formal and informal trust may add up to a 90 to 150 percent change in bilateral trade, depending on the legal system. Moreover our estimation results suggest that the causal relation runs p!rimarily from trust to trade, and that formal and informal trust are substitutes.
Keywords: F10; Z13; D23; K12; 330; trade; trust; transaction costs; gravity model; legal system; Transaktionskosten; Internationale Wirtschaft; Vertrauen; Gravitationsmodell